MORAL VALUE AND CHARACTER BUILDING EDUCATION FOLKLORE IN KARONESE “KAK TANGKO BUNGA” - Betty Rebina; Cindy Nathania Br. Sinuraya; Yenita Br. Sembiring (IDEAS: Journal on English Language Teaching and Learning, Linguistics and Literature, 2021)
Folklore is a traditional story that has been passed down from generation to generation which has an important role in moral value and character building.The purpose of this study is to describe the important of moral value to building good character though a folklore. This study is descriptive qualitative research design and all the date was collected from book, written document and other supporting information. The result and discussion of this study showed that there are five dominant values contain in folklore Kak Tangko Bunga such as give up beat work hard, help each other, don’t steal, do not lie, and don’t below others.From the research can be concluding that folklore Kak Tangko Bunga had many moral value and character building.